Dynamic Nexus between macroeconomic factors and CO2 emissions: Evidence from oil-producing countries - Gazi, Md. Abu Issa; Nahiduzzaman, Md.; Shaturaev, Jakhongir; Dhar, Bablu Kumar; Halim, Md. Abdul (Frontiers in Environmental Science, 2022)
Current literature conveys that in spite of conducting multiple studies to explore the influences of various macroeconomic factors both geographical and non-geographical on the CO2 emissions in different parts of the world, there is a scarcity of the same analyses in the oil-producing countries. In this study, we reveal a new dimension by investigating the dynamic linkage of climate change, economic growth, energy use, and agriculture & rural development to the CO2 emissions in oil-producing countries around the world. In doing so, we apply Johansen cointegration test, vector error correction model (VECM), pairwise Granger causality test, impulse response function (IRF), and some supportive models such as- generalized method of moments (GMM), and fixed-effect models. Our primary VAR-based models evidence that EUE, FDI, and TPR have both short-run and long-run casual consequences in CO2 emissions, while only long-run Granger causality is running from ALR, FAR, GDP, PGR, REC, and RPR to CO2 emissions. However, bidirectional associations are observed between CO2 to FDI and TPR; EUE to REC and TPR; and TPR to FDI and GDP. To demonstrate the significant impact, our secondary analysis tools GMM and fixed-effect regressions’ results disclose that high energy use and more domestic products significantly contaminate the environmental condition by increasing CO2 emissions in the atmosphere. Hence, our research provides great implications for the authorities of government, producers, businessmen, and general public in the oil-producing countries to ensure a sustainable environment by reducing energy use or alternating with renewable energies and emphasizing environmentally friendly products production over the long-run rather than conventional products production in the short-run.